2013
DOI: 10.11591/eei.v2i4.196
|View full text |Cite
|
Sign up to set email alerts
|

A New Block S-Random Interleaver for Shorter Length Frames for Turbo Codes

Abstract: In this paper, we have proposed a new design of interleaver based on S-random and block interleaver. The characteristics of both block and S-random interleaver are used by this proposed interleaver.  There is a large influence of free distance in turbo codes due to interleaving as it lowers the error floor. The free distance of turbo codes can be increased by designing interleaver with high spread. In this case, the overall spreading factor is increased significantly for smaller length frames also. The simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It has been found that one way to improve the performance of a turbo coded system is to use a good interleaver structure [5], [7], [8]. Therefore, interleaver design is the subject of numerous research projects and a number of algorithms have been developed [9]- [20]. It is asserted for turbo codes that interleavers with some randomness tend to perform better than their fully structured counterparts, especially for large block sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that one way to improve the performance of a turbo coded system is to use a good interleaver structure [5], [7], [8]. Therefore, interleaver design is the subject of numerous research projects and a number of algorithms have been developed [9]- [20]. It is asserted for turbo codes that interleavers with some randomness tend to perform better than their fully structured counterparts, especially for large block sizes.…”
Section: Introductionmentioning
confidence: 99%
“…A change in the length of interleaving requires another search of the interleaving pattern, which implies a more complex implementation. Furthermore, the generated interleavers, characterized by different lengths, should be stored separately in the memory [9], [10]. This causes a serious storage-related concern in a scenario in which many interleaving lengths need to be supported.…”
Section: Introductionmentioning
confidence: 99%